Análise dos efeitos do turnover na produtividade de processos de software tradicionais e híbridos - Carvalho, William Chaves de Souza (2012)
This dissertation presents an experimental case study conducted to aim to evaluate the effects of turnover on the software development projects productivity. To do so, they were collected and analyzed data from 27 software projects, developed in accordance with a process based on RUP or in a hybrid process that combines RUP and Scrum practices. The Stutzke s mathematical model was used to calculate the lost productivity due to the turnover of projects, taking into account duration of hirement, assimilation and mentoring. Data analysis was did based on a measurement model and performance indicators of product, people, technology, risk and quality. The results indicate that projects based on RUP lost an average of 5.25% of productivity due to the turnover while the hybrid process lose 11.86%. These results corroborates the research proposition that the project RUP are less likely than the hybrid projects to the effects of turnover on productivity. As suggestions to future researches the author states that the creation of Stutzke model extensions for predicting turnover in the early stages of the project, in order to help organizations to avoid projects loss of profitability.